When the elevator pitch meets the subject heading: How mixtures of other documents can describe what a document is about. Issue 1 (2014) - Organisciak, Peter; Twidale, Michael
ABSTRACT: We explore the concept of mixture descriptions in the context of film reviews. These descriptions of a film in terms of a combination of two or more other films. This very concrete approach to description can be contrasted with the abstractions typically used in subject headings or the names of genres. By exploring a dataset of film reviews, we uncover some of the features of mixture descriptions as they are used colloquially and investigate when and how they may prove useful. This form of description through combination is not specific to film, and we look at its potential as a bottom‐up, ludic form of document description.